Relationship Between Blood Pressure and Intraocular Pressure in Patients at the Ophthalmology Clinic of Hospital X Jakarta, Indonesia - Purwakusuma, Anindya Emiraryanti; Batubara, Lilian; Poerwanto, Eko (International Journal of Integrated Health Sciences, 2025)
Background: Hypertension, a prevalent and often asymptomatic condition, has been associated with various ocular disorders. Ocular hypertension, in particular, is a notable risk factor for glaucoma. Understanding the relationship between systemic blood pressure and intraocular pressure is important for early detection of ocular hypertension and prevention of vision-threatening complications.Objective: To analyze the relationship between blood pressure and intraocular pressure, as well as the association between hypertension and ocular hypertension. Methods: This observational analytical study used secondary data from the medical records of 74 patients at the ophthalmology clinic of Hospital X Jakarta, collected between January and March 2023. The sample was selected using purposive sampling. Results: Hypertension was observed in 30 individuals (41%), including 19 females (26%) and 11 individuals aged 70–79 years (15%). Ocular hypertension was reported in 17 individuals (23%), with ten (10) females (14%) and nine (9) individuals aged 60–69 years (12%). Chi-Square analysis showed a significant relationship between blood pressure and intraocular pressure, with a p-value of 0.004 (p<α=0.05). In addition, Spearman's test showed correlations between systolic blood pressure and intraocular pressure in both the right eye (r=0.395; p=0.001) and the left eye (r=0.290; p=0.012). Additionally, there were correlations between diastolic blood pressure and intraocular pressure in the right eye (r=0.234; p=0.045) and the left eye (r=0.230; p=0.049).Conclusion: The relationship between blood pressure and intraocular pressure is found to be significant in this study, suggesting that higher blood pressure levels are associated with an increased risk of elevated intraocular pressure.